Leveraging AI-Driven Personalization: The Future of Customer Experience in Digital Marketing - Falah, Asep Saful; Dewi, Lati Sari (Pascasarjana STIE Amkop Makassar, 2025)
Artificial Intelligence (AI) has reshaped digital marketing by enhancing personalized customer experiences through tools like chatbots, recommendation engines, and predictive analytics. This study uses a qualitative research methodology, employing a case study approach to explore AI-driven personalization's impact on customer engagement, satisfaction, and loyalty. Data were collected through semi-structured interviews with marketing experts, supplemented by observations and content analysis of digital platforms integrating AI personalization. Thematic analysis was applied to identify patterns and themes in AI’s role and the associated challenges around data privacy, ethical considerations, and potential biases within AI algorithms. Addressing these challenges requires transparency and balancing personalization with data security to maintain customer trust. Furthermore, this research highlights emerging trends, including the integration of AI with technologies like IoT and AR, that promise to revolutionize customer experiences. Future studies should focus on reducing algorithmic biases and expanding AI’s application to create ethical, sustainable personalization practices in digital marketing. Keywords: Artificial Intelligence, Digital Marketing, Personalization, Data Privacy